Upregulated Hexokinase-2 in Airway Epithelium Regulates Apoptosis and Drives Inflammation in Asthma via Peptidylprolyl Isomerase F - Zhen Tian; Hongyan Zheng; Yan Fan; Boyu Li; Zhenli Huang; Meijia Wang; Jixian Zhang; Jianping Zhao; Shanshan Wang; Jungang Xie (Cells, 2025)
Hexokinase catalyzes the first rate-limiting step glycolysis. However, the roles of hexokinase 2 (HK2) in asthma remain incompletely understood. This study aimed to investigate metabolic alterations in asthma, focusing on the expression, function and regulation of HK2. In this study, non-targeted metabolomics analysis of 20 asthma patients and 15 healthy controls identified metabolic alterations in asthma, particularly in the glycolytic pathways. Consistently, HK2 expression was elevated in both asthma individuals and mice with allergic airway inflammation. Airway epithelium–specific HK2 knockdown and pharmacological inhibition with 2-deoxy-D-glucose (2-DG) significantly attenuated airway inflammation and hyperresponsiveness in mice induced by ovalbumin/ lipopolysaccharide. Mechanistic analyses demonstrated that HK2 regulates epithelial apoptosis and inflammation via interaction with peptidylprolyl isomerase F (PPIF), independent of voltage-dependent anion channel 1 (VDAC1). Asthma is associated with metabolic reprogramming, characterized by alterations in lipid and glucose metabolism. These findings establish HK2 plays a crucial role in asthma pathogenesis by promoting airway epithelial apoptosis and inflammation in asthma, suggesting its potential as a therapeutic target.